The Crucial Presence of Private Higher Education in Latin America - Salto, Dante J. (International Higher Education, 2016)
During a recent "summit" meeting of leading Latin American higher education scholars and practitioners, key developments in Private Higher Education (PHE) became the topic of many meaningful discussions. This article reports on PHE and closely related issues, such as privatization and the comparison between the public and private sectors, highlighted at the summit.